Generalized Green’s functions for second-order discrete boundary-value problems with nonlocal boundary conditions - Paukštaitė, Gailė; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2012)
In this paper, generalized Green’s functions for second-order discrete boundaryvalue problems with nonlocal boundary conditions are investigated, where the necessary and sufficient existence condition of discrete Green’s function is not satisfied and nonlocal boundary conditions are described by linear functionals.